Penerapan Model Pembelajaran Project Based Learning (PJBL) Untuk Meningkatkan Keterampilan Berpikir Kritis Pada Pembelajaran IPAS - HUSAIN, MUH IKRAM; Ramlan, Ramlan Mahmud; Hartati, Hartati Saido (Global Journal Teaching Professional, 2024)
This research is motivated by the low critical thinking skills of students in science learning which is caused by the lack of student activities centered on problem solving, making learning less meaningful for students. This research aims to obtain an overview of improving students' critical thinking abilities and learning outcomes by applying the Project Based Learning model. The subjects of this research were class IV students at SD Negeri 30 Lembang consisting of 30 students. This research was carried out using the Classroom Action Research method. The instruments used include observation sheets, field notes, interviews and process tests and evaluations. The research results show that students' critical thinking abilities and learning outcomes using the Project Based Learning model in science and science learning in class IV of SD Negeri 30 Lembang have increased in each cycle. In cycle I, the average value of students' critical thinking ability process was 74.4, in cycle II 81.3, and in cycle III 84.4. Then the average student learning outcomes in cycle I was 57.6, in cycle II 70.83, and in cycle III 83. Based on the results of this research it can be concluded that there has been an increase in critical thinking skills and student learning outcomes and recommends the implementation of the Project model Based Learning is an alternative in improving critical thinking skills in science and science learning in elementary schools. Penelitian ini dilatarbelakangi oleh rendahnya kemampuan berpikir kritis siswa dalam pembelajaran IPAS yang disebabkan kurangnya aktivitas siswa yang berpusat pada pemecahan masalah membuat pembelajaran kurang bermakna bagi siswa. Penelitian ini bertujuan untuk memperoleh gambaran peningkatan kemampuan berpikir kritis siswa dan hasil belajar dengan menerapkan model Project Based Learning. Subyek penelitian ini adalah siswa kelas IV SD Negeri 30 Lembang terdiri dari 30 siswa. Penelitian ini dilaksanakan dengan metode Penelitian Tindakan Kelas. Instrumen yang digunakan meliputi lembar observasi, catatan lapangan, wawancara dan tes proses dan evaluasi. Hasil penelitian menunjukan bahwa kemampuan berpikir kritis dan hasil belajar siswa dengan menggunakan model Project Based Learning dalam pembelajaran IPAS di kelas IV SD Negeri 30 Lembang mengalami peningkatan pada setiap siklusnya. Pada siklus I, rata-rata nilai proses kemampuan berpikir kritis siswa sebesar 74,4, pada siklus II 81,3, dan pada siklus III 84,4. Kemudian rata-rata hasil belajar siswa pada siklus I sebesar 57,6, pada siklus II 70,83, dan pada siklus III 83. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa telah terjadi peningkataan kemampuan berpikir kritis dan hasil belajar siswa serta merekomendasikan penerapan model Project Based Learning ini sebagai salah satu alternatif dalam meningkatkan kemampuan berpikir kritis pada pembelajaran IPAS di sekolah dasar.